Suicide crises among women and mothers during and around the time of pregnancy: Prevalence and timing of initial contact with first responders and health services. (February 2023) - Meurk, Carla; Roberts, Susan; Lam, Michael; Wittenhagen, Lisa; Callaway, Leonie; Moss, Katherine; Lucke, Jayne; Barker, Ruth; Waterson, Elissa; Rawlinson, Catherine; Malmstrom, Natasha; Weaver, Edward; et al.
Objectives: Suicide is a leading cause of maternal mortality. Suicidality during and around the time of pregnancy can have detrimental impacts on a child's development and outcomes. This paper examines prevalence, demographic characteristics, and timing of initial contact with first responders and health services for a cohort of women who experienced suicidality during and around the time of pregnancy. Methods: Findings are drawn from the Partners in Prevention (PiP) study, a population-wide linked data set of suicide-related attendances by police or paramedics in Queensland, Australia. A sub-cohort of women was identified, who were between 6 months preconception and 2 years postpartum at the time of a suicide-related contact with police or paramedics (PiP-Maternal). Findings are compared to other girls and women who had a suicide-related contact with police or paramedics (PiP-Female). Prevalence, demographic characteristics, timing of contact with first responders and health services, re-presentations, and mortality are reported. Results: The PiP-Maternal cohort comprised 3020 individuals and 3400 births. Women in the PiP-Maternal cohort were younger, more likely to be of Aboriginal and/or Torres Strait Islander descent and live outside of a major city than the PiP-Female cohort. There were high rates of out-of-hours calls to police and ambulance, and similar perceived seriousness of the call between women in the PiP-Maternal and PiP-Female cohorts. Women in the PiP-Maternal cohort were less likely to be admitted to an emergency department within 24 hours, even after matching on covariates. Prevalence of suicidality for women who were pregnant and up to 2 years postpartum was 1.32% (95% CI = [1.27, 1.37]). Conclusion: Vulnerabilities and high rates of contact with police or paramedics, coupled with lower levels of follow-up, highlight the critical need to improve service responses for women with mental health needs during these phases of life.